2021
DOI: 10.1186/s12933-021-01411-6
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic role of RBP-4 and adiponectin in patients with peripheral arterial disease undergoing lower limb endovascular revascularization

Abstract: Background RBP4 is an adipokine with an established role in atherosclerosis, while adiponectin has unique anti-inflammatory properties. We investigated the association of RBP4 and adiponectin with the presence of symptomatic peripheral artery disease (PAD) and their possible prognostic role in major adverse cardiovascular events (MACE). Methods We enrolled 168 consecutive patients with symptomatic, established PAD, requiring revascularization by en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Ref. [ 19 ] recruited 168 patients aged 88 with peripheral artery disease (PAD) to study their potential prognostic function in major adverse cardiovascular events (MACE). It was found that an increase in RBP4 and decrease in adiponectin serum concentrations are independently linked with PAD appearance.…”
Section: Physiology and Pathophysiology Of Adiponectin On The Cardiov...mentioning
confidence: 99%
“…Ref. [ 19 ] recruited 168 patients aged 88 with peripheral artery disease (PAD) to study their potential prognostic function in major adverse cardiovascular events (MACE). It was found that an increase in RBP4 and decrease in adiponectin serum concentrations are independently linked with PAD appearance.…”
Section: Physiology and Pathophysiology Of Adiponectin On The Cardiov...mentioning
confidence: 99%
“…Obesity is closely related to physiological changes such as chronic inflammation and insulin resistance, and is the main cause of various metabolic diseases such as type 2 diabetes, fatty liver and hypertension ( 5 ). Previous studies have shown that in obese patients, adipose-related factors such as Retinol-Binding Protein-4 are significantly increased, which mediate the proliferation of vascular smooth muscle cells, and increase pro-inflammatory cytokines such as Tumor necrosis factor-alpha (TNF-alpha) and interleukins 1β, 2, 8, 10 (IL-1β, IL-2, IL-8, IL-10) and adhesion molecules such as vascular cell adhesion molecule 1, thereby aggravating the occurrence and development of PAD ( 5 , 27 ). In addition, the excessive weight of obese people will increase the mechanical compression of the arteries of the lower limbs, leading to damage to the blood vessel wall and promoting the progression of PAD ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Tet2 loss-of-function mutations have been shown in mice to increase IL-1β secretion from adipose tissue and aggravate age- and obesity-related insulin resistance [ 27 ]. Perivascular fat distribution [ 25 ] and adipokine signaling [ 28 ] influence the progression of PAD and adipose tissue-derived retinol binding protein 4 predicts major adverse events in PAD patients [ 28 ]. Thus, further studies should analyze whether and how adipose tissue signaling is affected by CH.…”
Section: Discussionmentioning
confidence: 99%